2012
DOI: 10.1097/mpg.0b013e3182555ba9
|View full text |Cite
|
Sign up to set email alerts
|

Laxative Treatment With Polyethylene Glycol Does Not Affect Lipid Absorption in Rats

Abstract: PEG does not affect lipid absorption nor steady-state plasma lipid levels in rats, although it accelerates the gastrointestinal transit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…It was shown that intestinal transit time decreased by 20%, but there was no change in TC and TG levels in rats given PEG 4000 at a non-diarrheal dose. 28 We also detected lower serum glucose levels in HFD + PEG 3350 mice, which was close to but not statistically significant (p = 0.0571). Similarly, in humans, it was observed that there was no difference between PEG 3350 and placebo in terms of glucose levels in the treatment of functional constipation for 2 weeks.…”
Section: Discussionsupporting
confidence: 60%
“…It was shown that intestinal transit time decreased by 20%, but there was no change in TC and TG levels in rats given PEG 4000 at a non-diarrheal dose. 28 We also detected lower serum glucose levels in HFD + PEG 3350 mice, which was close to but not statistically significant (p = 0.0571). Similarly, in humans, it was observed that there was no difference between PEG 3350 and placebo in terms of glucose levels in the treatment of functional constipation for 2 weeks.…”
Section: Discussionsupporting
confidence: 60%
“…Laxative treatment shortens intestinal transit time and is able to alter microbiota and BA homeostasis. In rats, the commonly used laxative polyethylene glycol (PEG) decreased BA dehydroxylation, increasing the amount of primary BAs in the BA pool [119]. Whole body Cftr knockout mice display a severe intestinal phenotype and need to be kept either on a liquid diet or a solid diet in combination with laxative.…”
Section: Modulating Bile Acid Homeostasis To Improve Gastrointestinal Outcomes In Cystic Fibrosismentioning
confidence: 99%
“…Fatty acids are not metabolized in the intestinal lumen, and we previously showed that the absorption and excretion of fatty acids is not changed by PEG (37), implying that fatty acids would not differentially influence fecal water cytotoxicity in PEG-treated rats. It should be realized that fecal water cytotoxicity has not been conclusively validated as a biomarker for colon cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Food and fluid intake and body weight were measured daily. Some of the rat characteristics have been reported in our previous paper, which reported on the aspects of PEG treatment on fat and cholesterol absorption (37).…”
Section: Cholate Kinetic Studymentioning
confidence: 99%